IMPROVING THE ABILITY OF MATHEMATIC PROBLEM SOLVING, MATHEMATIC CONNECTION AND SELF REGULATED LEARNING WITH JUNIOR HIGH SCHOOL STUDENTS THROUGH METAKOGNITIVE APPROACH - Asep Sopian; Jozua Sabandar (IKIP Siliwangi, 2018)
This study is a quasi experiment, aiming to describe the level of achievement of problem solving abilities, mathematical connections of students and the independence of junior high school students through metacognitive approach. The sample was chosen randomly from the class of all students of class IX in one of SMP Negeri in Karawang regency. The two class samples were chosen as control and experiment classes. Each of us uses a set of problem solving and mathematical connection tests and a set of learning independence scales. The study found that the attainment and improvement of problem solving ability and mathematical connection ability of students using metacognitive approach is better than the students whose learning is using normal learning in terms of the students' initial ability level. While different from the independence of students who learn learning using metacognitive approach is not better than students who use regular learning in terms of initial ability level of students. However, there is no interaction between the metacognitive approach and the student's initial ability level in generating problem solving skills and mathematical connections as well as learning independence which means that increased problem solving abilities and mathematical connections are largely influenced by the metacognitive approach.